Synthesis, DFT Study, Molecular Docking and Drug-Likeness Analysis of the New Hydrazine-1-Carbothioamide, Triazole and Thiadiazole Derivatives: Potential Inhibitors of HSP90 - Capan, Irfan; Servi, Suleyman; Yildirim, Ismail; Sert, Yusuf (Wiley-V C H Verlag Gmbh, 2021)
In this research, the new hydrazine-1-carbothioamides (IC32 and IC34) having unsubstituted benzimidazole skeleton were converted to 1, 2, 4-triazole derivatives (IC42 and IC44) by N-cyclization reaction using the microwave-assisted synthesis method in the basic medium with high efficiency in a short time. 2-Amino-1,3,4-thiadiazole derivatives (IC52 and IC54) were obtained from the carbothioamides in the acidic medium by S-cyclization using the conventional method. The structure of all compounds was confirmed by FT-IR, H-1 NMR, and C-13 NMR spectroscopic techniques. The optimized structures, theoretical NMR shielding values in DMSO-d(6) solvent, the frontier molecular orbital, molecular electrostatic potential, and non-linear optical properties of these molecules were calculated in the Gaussian 09 W package program by using DFT method/B3LYP function and 6-311++G (d, p) basis set. All calculations except NMR calculations were performed in the gas phase and the obtained results were interpreted within the related sections. The discovery of new drugs is of great importance in combating health problems and improving the quality of human life. In the light of this information, molecular docking with Autodock Vina and physicochemical calculations with the SwissADME server were performed at the end of the article. Therefore, the inhibiting potential of the ligands containing different groups in their structure was investigated for the first time in this study.
Keywords: Benzimidazole; carbothioamide; 1; 2; 4-triazole-5(4H)-thione; 2-amino-1; 3; 4-thiadiazole; DFT; Molecular docking